School Phobia - Clark, Norman (1971)
School phobia is a more persistent form of the common childhood wish to get the occasional day off school, and manifests in both acute and chronic forms. The child's dependency on parents and home surroundings should be assessed and the parents taught how to cope with the various developmental milestones in the child's life, together with the separation fears these will produce. Parents must be firm and the assistance of teachers or school guidance counsellors is very helpful.